The Effect of Knowledge and Understanding Taxation, Quality of Tax Services, and Tax Awareness on Personal Tax Compliance - Ayu Aulia Oktaviani; Florencia Trisna Juang; Dwi Ayu Kusumaningtyas (Universitas Trisakti, 2017)
The purpose of this study is to find out a significant influence between Knowledge and Understanding of Taxation, Tax Service Quality, and Tax Awareness on the Compliance of Individual Taxpayers registered at the KPP of Jakarta Penjaringan. The research method used is multiple regression analysis. The data used are primary data; a sample is determined by convenience sampling method, data collected using a questionnaire. Respondents in this study amounted to 100 people. The results of this study are knowledge and understanding of taxation, tax service quality, and tax awareness have a significant positive effect on the compliance of individual taxpayers. This study also proves that tax awareness, knowledge, and understanding of taxation, and tax service quality are jointly influential towards individual taxpayer compliance.